Study on Thermal Performance Measurement and Construction of Passive Exterior Wall with Low Energy: Teaching and Laboratory Building of Shandong Jianzhu University - Yirui Lan; Ran Zou (Advances in Materials Science and Engineering)
It can provide theoretical support for the optimal design of low-energy walls by measuring the actual thermal conditions inside the walls of passive low-energy buildings and studying the rationality of the wall structure design. Taking the teaching and laboratory building of Shandong Jianzhu University as an example, this paper explores the method of using temperature and humidity sensor to measure the air temperature and humidity inside the wall to represent the solid temperature and humidity of the wall. Based on the measured data and calculation results, the rationality of the structure of the test external wall is analyzed from four aspects: the performance of insulation, the moisture drain performance of wall, the ability of preventing the penetration of the hot and humid air of the inner wall, and the waterproof performance of the outer wall. Results show that the external wall structure of polystyrene board (200 mm thick) for external insulation and thin plastering has good practical operation effect in three aspects of thermal insulation, internal moisture discharge, and external wall waterproof, which basically meets the design requirements of external wall of passive house in Germany. In terms of moisture protection of the inner wall, the inner wall of cement mortar (15 mm thick) may not be able to effectively prevent the infiltration of indoor hot and humid air. Thus, the insulation layer should be added into the external wall. In addition, the moisture inside the wall is obviously affected by the season. The drain performance of moisture inside the wall mainly occurs in the sweltering heat, and the drain direction is from the indoor side to the outdoor side. In the external insulation structure, there are two layers of graphite polystyrene plate (100 mm thick), and the insulation effect of polystyrene plate near the outdoor side is better than that near the indoor side. The combination of anticrack mortar (5 mm thick) and paint cannot completely prevent the infiltration of rainwater, but the infiltration of rainwater in the wall will be quickly discharged in a short time.